Solve for x
x = \frac{\sqrt{13} + 11}{6} \approx 2.434258546
x = \frac{11 - \sqrt{13}}{6} \approx 1.232408121
Graph
Share
Copied to clipboard
3x^{2}-11x+10=1
Use the distributive property to multiply x-2 by 3x-5 and combine like terms.
3x^{2}-11x+10-1=0
Subtract 1 from both sides.
3x^{2}-11x+9=0
Subtract 1 from 10 to get 9.
x=\frac{-\left(-11\right)±\sqrt{\left(-11\right)^{2}-4\times 3\times 9}}{2\times 3}
This equation is in standard form: ax^{2}+bx+c=0. Substitute 3 for a, -11 for b, and 9 for c in the quadratic formula, \frac{-b±\sqrt{b^{2}-4ac}}{2a}.
x=\frac{-\left(-11\right)±\sqrt{121-4\times 3\times 9}}{2\times 3}
Square -11.
x=\frac{-\left(-11\right)±\sqrt{121-12\times 9}}{2\times 3}
Multiply -4 times 3.
x=\frac{-\left(-11\right)±\sqrt{121-108}}{2\times 3}
Multiply -12 times 9.
x=\frac{-\left(-11\right)±\sqrt{13}}{2\times 3}
Add 121 to -108.
x=\frac{11±\sqrt{13}}{2\times 3}
The opposite of -11 is 11.
x=\frac{11±\sqrt{13}}{6}
Multiply 2 times 3.
x=\frac{\sqrt{13}+11}{6}
Now solve the equation x=\frac{11±\sqrt{13}}{6} when ± is plus. Add 11 to \sqrt{13}.
x=\frac{11-\sqrt{13}}{6}
Now solve the equation x=\frac{11±\sqrt{13}}{6} when ± is minus. Subtract \sqrt{13} from 11.
x=\frac{\sqrt{13}+11}{6} x=\frac{11-\sqrt{13}}{6}
The equation is now solved.
3x^{2}-11x+10=1
Use the distributive property to multiply x-2 by 3x-5 and combine like terms.
3x^{2}-11x=1-10
Subtract 10 from both sides.
3x^{2}-11x=-9
Subtract 10 from 1 to get -9.
\frac{3x^{2}-11x}{3}=-\frac{9}{3}
Divide both sides by 3.
x^{2}-\frac{11}{3}x=-\frac{9}{3}
Dividing by 3 undoes the multiplication by 3.
x^{2}-\frac{11}{3}x=-3
Divide -9 by 3.
x^{2}-\frac{11}{3}x+\left(-\frac{11}{6}\right)^{2}=-3+\left(-\frac{11}{6}\right)^{2}
Divide -\frac{11}{3}, the coefficient of the x term, by 2 to get -\frac{11}{6}. Then add the square of -\frac{11}{6} to both sides of the equation. This step makes the left hand side of the equation a perfect square.
x^{2}-\frac{11}{3}x+\frac{121}{36}=-3+\frac{121}{36}
Square -\frac{11}{6} by squaring both the numerator and the denominator of the fraction.
x^{2}-\frac{11}{3}x+\frac{121}{36}=\frac{13}{36}
Add -3 to \frac{121}{36}.
\left(x-\frac{11}{6}\right)^{2}=\frac{13}{36}
Factor x^{2}-\frac{11}{3}x+\frac{121}{36}. In general, when x^{2}+bx+c is a perfect square, it can always be factored as \left(x+\frac{b}{2}\right)^{2}.
\sqrt{\left(x-\frac{11}{6}\right)^{2}}=\sqrt{\frac{13}{36}}
Take the square root of both sides of the equation.
x-\frac{11}{6}=\frac{\sqrt{13}}{6} x-\frac{11}{6}=-\frac{\sqrt{13}}{6}
Simplify.
x=\frac{\sqrt{13}+11}{6} x=\frac{11-\sqrt{13}}{6}
Add \frac{11}{6} to both sides of the equation.
Examples
Quadratic equation
{ x } ^ { 2 } - 4 x - 5 = 0
Trigonometry
4 \sin \theta \cos \theta = 2 \sin \theta
Linear equation
y = 3x + 4
Arithmetic
699 * 533
Matrix
\left[ \begin{array} { l l } { 2 } & { 3 } \\ { 5 } & { 4 } \end{array} \right] \left[ \begin{array} { l l l } { 2 } & { 0 } & { 3 } \\ { -1 } & { 1 } & { 5 } \end{array} \right]
Simultaneous equation
\left. \begin{cases} { 8x+2y = 46 } \\ { 7x+3y = 47 } \end{cases} \right.
Differentiation
\frac { d } { d x } \frac { ( 3 x ^ { 2 } - 2 ) } { ( x - 5 ) }
Integration
\int _ { 0 } ^ { 1 } x e ^ { - x ^ { 2 } } d x
Limits
\lim _{x \rightarrow-3} \frac{x^{2}-9}{x^{2}+2 x-3}